Selection of European larch provenances based on productivity and economic values - J. Kobliha; J. Stejskal; M. Lstibůrek; R. Marušák; M. Slávik (Journal of Forest Science, 2013)
Productivity of individual European larch provenances was evaluated on the basis of height and diameter growth and volume production at the age of 40 years. This work was focused on identifying differences among European larch provenances using a growth simulation model (SIBYLA). Based on the growth simulations, all selected provenances had greater mean height, stem diameter and stem volume at the age of 120 years than the control seed source. Provenance 49 (Krnov-Loučky, Jeseníky, CZ) had the greatest height growth and volume, but it ranked the fourth in diameter. Provenances 16 (Cavalese, Italy) and 71a (Jaroměřice-Chroustov, Vysočina, CZ) ranked the highest in stem diameter and volume growth. With respect to a different tree number per hectare these characteristics are different when expressed as total per-hectare volume production. Despite that fact, the control material is inferior also in this category. In addition to production, timber assortment and economic balance of the same provenances at the age of 120 years were evaluated.